Characterization of Mineral Macronutrients Kinetics During Faeces-Based Composting Process in Composting Toilets - Effebi Kokoh Rose; Kouame Bene Lucien; Kouassi Yeboua Firmin; Kouadio Louis; Gone Droh Lancine (European Scientific Journal, ESJ, 2017)
Given the environmental concerns and public health risks that could arise, the use of composting toilets by-products requires compliance with quality standards beforehand. However, such quality assessment is often lacking for those by-products in rapidly urbanizing sub-Saharan cities. This study examines the kinetics of major mineral nutrients [i.e., nitrogen (N), phosphorus (P), and potassium (K), which are among the key indicators of a compost’s stability] during a composting process of fecal matters from composting toilets. The monitoring was carried out at Abobo-Sagbé, Abidjan, Côte d’Ivoire over a 4.5-month period. Feces-based compost data collected on 6 different dates (i.e., on the 28th , 48th , 62nd , 76th , 90th , and 133nd day from the start of the composting process) were analyzed, and screened for their contents in total N, total P and K. Results showed a rapid decrease of the content of all three elements during the first 29 days, followed by a sharp increase, especially for P and K, and then a quite stable variation during the last 2 months of the monitoring. Variations of C/N ratio during the study were similar to those reported previously. Although the proportions of P and K were satisfactory at the end of the monitoring period, the final C/N ratio was relatively high compared to suitable ratios characterizing mature composts, suggesting therefore additional time may be required before any use of the compost as fertilizer in agriculture.